THE STATE POLICY OF UKRAINE IN THE FIELD OF CONTINUOUS ECONOMIC EDUCATION - Bezliudnyi, Oleksandr; Kirdan, Oleksandr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the paper is to substantiate the main components and factors of the state policy of Ukraine that influence the development of continuous economic education and to outline ways of its improvement. Achieving the aim of the research study made it possible to use the following methods: comparative and structural-logical analysis, classification, systematization, generalization. Results of the research. The essence of continuous economic education, its role and importance at national and world levels are considered. On the basis of a structural-logical analysis and systematization, the current normative-legal acts of Ukraine are grouped into the following groups: strategic guidelines for the development of continuous economic education; documents regulating the content of continuing economic education; regulatory and legal regulation of state supervision measures in the field of education and quality assurance. The main components of the state policy of Ukraine that influence the development of continuous economic education are defined, namely: development of the system of continuous economic education throughout life; creation of equal opportunities for formal, informal and non-formal economic education for all citizens of Ukraine; formation of values and social economic responsibility; a policy of enhancing the culture of teaching, learning and assessment. The dynamics of applicants for higher economic education of bachelor's and master's degrees are analysed.